Revision of Banded Knifefishes of the Gymnotus carapo and G. tigre clades (Gymnotidae Gymnotiformes) from the Southern Neotropics - Craig, Jack M.; Malabarba, Luiz R.; Crampton, William G. R.; Albert, James S. (Zootaxa, 2018)
Banded Knifefishes (Gymnotus, Gymnotidae) comprise the most species-rich, ecologically tolerant (eurytopic), and geographically widespread genus of Neotropical electric fishes (Gymnotiformes), with 40 valid species occupying most habitats and regions throughout the humid Neotropics. Despite substantial alpha-taxonomic work in recent years, parts of the genus remain characterized by taxonomic confusion. Here we describe and delimit species of the G. carapo and G. tigre clades from the southern Neotropics, using body proportions (caliper-based morphometrics), fin-ray, scale and laterosensory-pore counts (meristics), quantitative shape differences (geometric morphometrics), osteology, color patterns and electric organ discharges. We report these data from 174 Gymnotus specimens collected from 100 localities throughout the southern Neotropics, and delimit species boundaries in a multivariate statistical framework. We find six species of the G. carapo clade (G. carapo australis, G. cuia n. sp., G. chimarrao, G. omarorum, G. pantanal, and G. sylvius), and two species of the G. tigre clade (G. inaequilabiatus and G. paraguensis) in the southern Neotropics. The new species G. cuia is readily distinguished from the morphologically similar and broadly sympatric G. c. australis by a shorter head and deeper head and body, and from the morphologically similar and sympatric G. omarorum by fewer lateral-line ventral rami and fewer pored lateral-line scales anterior to the first ventral ramus. We also review the geographic distributions of all eight species of the G. carapo and G. tigre clades in the southern Neotropics, showing that G. cuia is the most widespread species in the region. These results affirm the importance of understanding the structure of variation within and between species, both geographic and ontogenetic, in delimiting species boundaries.